2011
DOI: 10.1007/s11250-011-9938-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among Anaplasma marginale parasitemia and markers of oxidative stress in crossbred calves

Abstract: The present study was designed to determine the correlations among Anaplasma marginale parasitemia and markers of oxidative stress in crossbred calves. Blood was collected from 11 crossbred calves infected with A. marginale along with 11 healthy crossbred calves as controls for determination of hematology and oxidative stress indicators. Percentage of parasitemia in infected calves varied from 0.8% to 6.0%. The values of hematological indicators and antioxidant enzymes were decreased, whereas erythrocytic lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
6
9
0
Order By: Relevance
“…These results were similar to those reported by others (De et al 2012;Abdel Hamid et al 2014). It was suggested that the severe anaemia could be attributed to immune-mediated destruction of parasitised and non-parasitised erythrocytes (De et al 2012). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were similar to those reported by others (De et al 2012;Abdel Hamid et al 2014). It was suggested that the severe anaemia could be attributed to immune-mediated destruction of parasitised and non-parasitised erythrocytes (De et al 2012). …”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, the efficiency of traditional microscopic examination of Giemsa-stained blood films in detecting carrier animals with low rates of parasitaemia is very limited (Younis et al 2009). The clinical findings presented in this study were in part similar to those previously described (De et al 2012;OIE 2012;El-Ashker et al 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The infection leads to a drastic increase in the number of infected erythrocytes. These cells are then phagocytosed by reticuloendothelial cells leading to hemolytic anemia and icterus [ 7 ]. Clinical signs of A. marginale infection include anorexia, dyspnea, tachycardia, hemolytic anemia, jaundice, lacrimation, salivation, fever, fatigue, diarrhea, frequent urination, and abortion.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in indices of oxidative stress are recorded in parasitic diseases. The role of erythrocytic peroxidation in the pathogenesis of several hemiparasitic infections is well recognized [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…After infection, parasitemia increases until the hemolytic crisis, frequently with more than 50% of RBCs infected 18 . The number of infected erythrocytes increases drastically and phagocytosis by reticulo-endothelial cells of parasitized erythrocytes lead to development of hemolytic anemia and icterus 19 . Serum biochemical parameters such as aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), concentrations are indicators of hepatic function.…”
Section: Introductionmentioning
confidence: 99%